(untitled) (Medical Forum Monthly, 2024)
Objective: To study the comparative effects of aqueous Neem leaf extract with N-Acetylcysteine on the basis of liver enzymes (AST, ALT, ALP) and histopathological changes in paracetamol induced liver damage. Study Design: Experimental / Interventional comparative study. Place and Duration of Study: This study was conducted at the Pharmacology Department, Al-Tibri Medical College, Karachi from January 2015 to June 2015. Materials and Methods: Total sixty (60) albino rats of either gender were equally divided into four (04) respective groups. Each group comprised of 15 animals. Animals of group A were considered as un-treated or control group. In group B animals were treated with a single dose 2mg/kg b/w of paracetamol orally. Group C animals with neem extract 500mg/kg b/w orally for 15 days along with oral administration of 2mg/kg b/w paracetamol. In group D, animals were treated with same dose of paracetamol and 140mg/kg b/w of N-Acetylcysteine intraperitoneal for 06 days. Results: The results showed that the liver enzymes were markedly increased in paracetamol treated group of animals, but decreased when animals were treated with Neem and N-Acetylcesteine. The mean serum level of enzymes such as AST, ALT and ALP were found to be more i.e, 110.8, 40.00 and 444.33 respectively but the mean level decreased in the animals of group C such as 29.133, 20.00 and 240.33. However, liver enzymes were also reduced in group D but their levels were relatively lesser than animals of group C. Regarding histopathological review, the tissue sections showed necrotic hepatocytes, congestion in blood vessels in paracetamol treated group of animals. However, the changes were found significantly reversed in group C and group D, but marked changes were seen in animals of group C as compared to N-Acetylcysteine treated group of animals. Conclusion: Paracetamol is a hepatotoxic drug causing histomorphological damage in liver along with alteration in the level of Liver enzymes. Azadirachta indica leaves have given better results compared to N-Acetylcysteine, on the basis of significant differences in biochemical parameters.